2016
DOI: 10.1007/s00464-016-4831-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two endoscopic closures: over-the-scope clip (OTSC) versus KING closure (endoloop + clips) in a randomized long-term experimental study

Abstract: Both OTSC and KING closures offer a long-term reliable seal of a gastrointestinal perforation without stenosis or fistulas. KING closure provides long-term histologically superior healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Full‐thickness defect closure using clips and special devices may still result in complete leakage of fluids and gases. Therefore, devices other than clips have also been developed 91,114–116 . The endoscopic suturing device (Overstitch; Apollo Endosurgery, Austin, TX, USA) can completely close full‐thickness defects by passing a thread through the mucosa without using a clip 117–119 .…”
Section: Desirable Features Of Clip‐based Closure Methods or Special ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Full‐thickness defect closure using clips and special devices may still result in complete leakage of fluids and gases. Therefore, devices other than clips have also been developed 91,114–116 . The endoscopic suturing device (Overstitch; Apollo Endosurgery, Austin, TX, USA) can completely close full‐thickness defects by passing a thread through the mucosa without using a clip 117–119 .…”
Section: Desirable Features Of Clip‐based Closure Methods or Special ...mentioning
confidence: 99%
“…Therefore, devices other than clips have also been developed. 91,[114][115][116] The endoscopic suturing device (Overstitch; Apollo Endosurgery, Austin, TX, USA) can completely close full-thickness defects by passing a thread through the mucosa without using a clip. [117][118][119] Another method of suturing the mucosa uses a double-channel endoscope with an absorbable barbed suture (V-loc 180 3-0; Covidien, Mansfield, MA, USA) and a needle with a holder.…”
Section: Full-thickness Defect Closure Using Clips and Special Devicesmentioning
confidence: 99%
“…However, this method can fail in some cases 1 2 3 . Studies have reported that the King closure is a safe technique and provides superior long-term histological healing outcomes compared with OTS clipping 4 5 . In conclusion, perifistular mucosal ablation followed by the single loop-and-clips technique appears to be an effective approach for the treatment of complex fistulas.…”
Section: Figmentioning
confidence: 99%
“…Als experimentell zu werten ist hingegen der Einsatz endoskopischer Nahtsysteme [1]. Gleiches gilt für die Anwendung des mithilfe von Metallclips geführten Endoloops [1,29,30]. Wegen der hohen Variabilität der zu versorgenden Läsionen erfordert das endoskopische Vorgehen ein hohes Maß an Erfahrung seitens des ausführenden Teams, sowohl hinsichtlich der situationsadaptierten Verfahrenswahl als auch in Bezug auf die technischen und handwerklichen Aspekte [1].…”
Section: Introductionunclassified